PPE51 Is Involved in the Uptake of Disaccharides by Mycobacterium tuberculosis - Małgorzata Korycka-Machała; Jakub Pawełczyk; Paulina Borówka; Bożena Dziadek; Anna Brzostek; Malwina Kawka; Adrian Bekier; Sebastian Rykowski; Agnieszka B. Olejniczak; Dominik Strapagiel; Zbigniew Witczak; Jarosław Dziadek (Cells, 2020)
We have recently found that selected thio-disaccharides possess bactericidal effects against Mycobacterium tuberculosis but not against Escherichia coli or Staphylococcus aureus. Here, we selected spontaneous mutants displaying resistance against the investigated thio-glycoside. According to next-generation sequencing, four of six analyzed mutants which were resistant to high concentrations of the tested chemical carried nonsynonymous mutations in the gene encoding the PPE51 protein. The complementation of these mutants with an intact ppe51 gene returned their sensitivity to the wild-type level. The uptake of tritiated thio-glycoside was significantly more abundant in wild-type Mycobacterium tuberculosis compared to the strain carrying the mutated ppe51 gene. The ppe51 mutations or CRISPR-Cas9-mediated downregulation of PPE51 expression affected the growth of mutant strains on minimal media supplemented with disaccharides (maltose or lactose) but not with glycerol or glucose as the sole carbon and energy source. Taking the above into account, we postulate that PPE51 participates in the uptake of disaccharides by tubercle bacilli.